Electronic Gallipoli? - Cobb, Adam (Australian Journal of International Affairs)
Deals with the risks and benefits related to information technology. Accidents and threats related to information technology; Probable consequences of nationwide computer breakdowns on January 1, 2000; Details on information warfare and national security; Information on the National Information Infrastructure.